MAURICE MERLEAU-PONTY AND THE RESULTS OF HIS THOUGHTS - Ali Mursyid Azisi (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2020)
Maurice Merleau-Ponty is a philosopher of phenomenology who came from France. From some of his thoughts on several matters, in this case concerning the primacy of perception, the body as a subject, masochism, the unity of taste, and the ambiguity of the experience of taste, it is an interesting discussion to study, especially among academics. Not only that, from the results of his thinking, Merleau-Ponty is also called the "ignorant guide" by the Western world. From the results of his thinking, Merleau places the body as a subject that is absolutely owned by humans, while the environment and what the five senses perceive are called objects. From the opinions expressed, it is hoped that it will be useful for many circles. In collecting data in this article using qualitative methods with a review of relevant literature and accompanied by examples that can facilitate understanding. It is very important to explore more about Merleau-Ponty's thoughts, which in this case will be studied further in an article entitled Maurice Merleau-Ponty and the Results of His Thought. In this way, this article is hoped to be able to help academics discover the uniqueness of the thoughts and opinions of Maurice Merleau-Ponty.